PROVISIONAL CHECKLIST OF GINGERS FROM TAMA ABU PF - Aimi Syazana, Sedek; Meekiong, Kalu; Syauqina, M.Y.; Shabdin, Z.; Miraadila, M.I.; Ivy Geradlyn, N.; Yazid, K.; Nur Safinas, J. (2019)
Zingiberaceae species are a diverse group of rhizomatous, aromatic perennial herbs with the centre of diversity in South-east Asia. The Zingiberaceae diversity in the Tama Abu Production Forest (TAPF) documented in this paper is a result of the survey during the Heart of Borneo (HoB) Scientific Expedition 2017. A total of 44 species belonging to 12 genera and 2 tribes were collected and recorded. The tribe Alpinieae represented by 8 genera and 30 species whilst tribe Zingiberaea with 4 genera and 14 species. Amomum anomalum, Amomum dimorphum, Etlingera brevilabrum, Etlingera coccinea, Globba atrosanguinea, Hornstedtia havilandii, Plagiostachys strobilifera and Zingiber sp. nov. are considered as common.